2003
DOI: 10.1177/000841740307000303
|View full text |Cite
|
Sign up to set email alerts
|

A Secondary Guy: Physically Disabled Teenagers in Secondary Schools

Abstract: Description générale. Cette étude avait pour but d'examiner les perceptions et les expériences d'adolescents ayant des déficiences physiques qui fréquentent des écoles secondaires régulières. L'étude portait particulièrement sur l'intégration sociale de ces jeunes et sur les facteurs qui agissent sur cette intégration. L'intégration sociale a été définie comme un sentiment d'appartenance au milieu scolaire. Méthodologie. Une approche phénoménologique a été utilisée pour examiner le point de vue des adolescents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
40
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 42 publications
5
40
0
Order By: Relevance
“…If you had a real mate you wouldn't care you would just help. (P4) These findings correspond with Doubt and McColl (2003) who found that the extrinsic factors such as the attitudes and behaviours of non-disabled peers were barriers to social integration. However, what is of note here is how that isolation made the participants feel.…”
Section: Social Integrationsupporting
confidence: 84%
“…If you had a real mate you wouldn't care you would just help. (P4) These findings correspond with Doubt and McColl (2003) who found that the extrinsic factors such as the attitudes and behaviours of non-disabled peers were barriers to social integration. However, what is of note here is how that isolation made the participants feel.…”
Section: Social Integrationsupporting
confidence: 84%
“…This is not a new discovery, although this has not been reported previously by parents (Doubt & McColl, 2003;Goodwin & Watkinson, 2000). Mothers observed the restrictive nature of physical environments (e.g., access to weight room, grass) on their children's participation in physical education.…”
Section: Andrea Explainedmentioning
confidence: 53%
“…The efficacy of inclusion as an educational service has been studied from the perspectives of special and general education teachers, administrators, and students (Bain & Dolbel, 1991;Bennett, Deluca, & Bruns, 1997;Doubt & McColl, 2003;Giangreco, Dennis, Cloninger, Edelman, & Schattman, 1993;Wilson, 1999). Only recently, however, has attention been given to the role of parents of children with disabilities in the inclusive process.…”
Section: Parents' Views Of Inclusionmentioning
confidence: 99%
“…Isakson and Jarvis (1999) found that stressors decreased school belonging among students in their transition to high school, whereas support from parents and peers predicted increased school belonging. For students with disabilities, peer-related stressors, such as exclusion by peers, decreased school belonging, and peer and staff support increased school belonging (Doubt & McColl, 2003). African American and urban samples had lower perceived school belonging compared to European American and suburban samples.…”
Section: School Belongingmentioning
confidence: 93%